Assimilation and Metabolism of Exogenous Organic Compounds by the Strict Autotrophs Thiobacillus thioparus and Thiobacillus neapolitanus - Johnson, Emmett J. (1969)
The assimilation and utilization of the individual carbon atoms of pyruvate and acetate by cells of Thiobacillus thioparus and T. neapolitanus, in the presence and absence of an energy source, were studied by use of radioactive substrates. Both organisms produced (14)CO(2) from (14)C-labeled pyruvate, but more came from carbon 1 than from carbons 2 or 3. The conversion of the carbons of acetate to CO(2) by both organisms was much less than that from any of the pyruvate carbons. When labeled pyruvate and acetate were incubated with these organisms, small amounts of radioactivity were found in the tricholoacetic acid-soluble material, nucleic acids, and lipids, and larger amounts were found in the protein fraction. The composition of the incubation medium affected the amount of utilization and incorporation of labeled substrates by both organisms. The presence of an exogenous energy source (Na(2)S(2)O(3)) suppressed incorporation of the labeled substrates into various cellular components by T. thioparus, but enhanced incorporation by T. neapolitanus. When (14)C-pyruvate was used as a substrate, as many as 12 radioactive compounds were found in the water-soluble fraction in the experiments with T. neapolitanus, whereas no more than three radioactive compounds were detected in this fraction in the experiments with T. thioparus. Of the total (14)C activity found in the water-soluble fractions, malic acid contained the highest percentage. These findings are discussed in light of the overall metabolism of these two sulfur-oxidizing obligate chemoautotrophs, as well as in relation to the biochemical basis of chemoautotrophy.